Seasonal dynamics and functioning of the Sylt-Rømø Bight, northern Wadden Sea. (5th April 2018) - de la Vega, Camille; Horn, Sabine; Baird, Dan; Hines, David; Borrett, Stuart; Jensen, Lasse Fast; Schwemmer, Philipp; Asmus, Ragnhild; Siebert, Ursula; Asmus, Harald
Abstract: The Wadden Sea undergoes large seasonal changes in species abundance and biomass comprising its complex food web. This study examined four carbon food web models of the Sylt-Rømø Bight, one for each season. Each flow model consisted of 66 compartments depicting the respective biomass and energy budget of each ecosystem component and the flows between them. Ecological network analysis (ENA), a set of algorithms to evaluate the functioning of ecological networks, was used to assess the seasonal variability in the system properties of the Sylt-Rømø Bight food webs. We used an uncertainty analysis to quantitatively evaluate the significance of inter-seasonal differences. Clear seasonal variation was observed in most of the whole system indicators such as the flow diversity, the effective link density and the relative redundancy which varied by 12.8%, 17.3% and 10.3% respectively between the highest in summer and the lowest during fall and winter, whereas the relevant ascendency ratio was the highest in winter during the least active months. Other indices such as the average mutual information index, which fluctuated between 1.73 in fall and 1.79 in spring, showed no significant variation between seasons. Results from ENA have great potential for ecosystem management, as it provides a holistic assessment of the functioning of ecosystems. Graphical abstract: Image 1 Highlights: We modelled the food web of the Sylt-Rømø Bight seasonally. We run an uncertainty analysis on these four seasonal food web models. Most of the whole system indicators reflected the seasonal variation of the biomass. The system had higher ability to cope with disturbances in summer compared to winter. An annual model would be sufficient for management purpose.